Which behavioral patterns score points in taekwondo matches? An analysis of the Roma 2019 World Grand Prix finalists - Rodríguez, Y. Q.; Apollaro, G.; Fúnez, C.; Faelli, E.; Hernández-Mendo, A.; Morales-Sánchez, V.; Falcó, C. (Frontiers in Sports and Active Living, 2025)
Introduction: Observational methodology facilitates the study of situational factors in taekwondo matches, examines observable technical-tactical behaviors, and reveals various relationships, thus generating behavioral patterns. The aim of this study was to examine the technical-tactical scoring actions in the final matches of the Roma 2019 World Taekwondo Grand Prix, using polar coordinate analysis and function estimation.